Cow size and milk level: results of a simulation program - Schalles, R.R.; Bourdon, R.M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A simulation program was used to evaluate nine genotypes of cattle based on, cow size and milk production. Return per cow unit using current economics is given. The larger, heavy milking cows were more than twice as profitable on a ranch basis than the small, low milking cows.
Keywords: Beef; Milk production; Cow size